Infectious Angiogenesis—Different Pathways, the Same Goal. (November 2016) - Urbanowicz, Maria; Kutzner, Heinz; Riveiro-Falkenbach, Erica; Rodriguez-Peralto, Jose L.
Abstract : Abstract: Infectious angiogenesis is the biological response of neoangiogenesis induced by infectious organisms. The authors present 3 exemplary entities which show paradigmatic clinico-pathological settings of infectious angiogenesis: Bacillary angiomatosis, Orf (ecthyma contagiosum), and Kaposi sarcoma. The authors review the literature and elucidate etiopathogenetic pathways leading to the phenomenon of neovascularization stimulated by infectious organisms. The authors describe the clinical and histological pictures, interactions between microorganisms and host cells, and changes that occur within cellular structures, as well as angiogenic factors that underpin infectious angiogenesis. The importance of chronic inflammation and tumor angiogenesis is emphasized.